SAS and special forces fitness training an elite workout program for body and mind - Wiseman, John (Amber Books, 2017)
"The SAS is one of the world's greatest military elite units and its soldiers are renowned for their ability to cope when under great physical and mental stress. With this book readers can acquire the unique range of skills taught to members of the British Special Air Service to help them succeed in the modern world. SAS Fitness Training features illustrated exercises for improving strength, stamina, and agility; advice on diet and nutrition; and chapters on mental agility and self-defense teach readers how to overcome their daily challenges, the SAS way."